An evaluation of Antyodaya Programme in Uttar Pradesh : a study of selected households in districts Chamoli and Jhansi - Vaish, R. R. (Research study (University of Delhi. Agricultural Economics Research Centre), 1982)
On domestic economic assistance for the integrated rural development.